Analisis Usahatani dan Pemasaran Cabai Rawit (Capsicum Frutescens. L) di Kebon Enha Lima Sei Kijang Kabupaten Pelalawan Provinsi Riau - Ernawati; Wahyudi Zikri; Hasanudin; Adriansyah; Khairudin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Cultivating cayenne pepper is a profitable agribusiness venture that is worth developing with good production management, pest and disease control, and efficient use of resources. The main profits come from high yields and the relatively good market value of cayenne pepper. The research location is in Kebon Enha Lima, Pelalawan Regency. The objectives of the study were to examine the technical aspects of cayenne pepper cultivation, cayenne pepper farming, and cayenne pepper marketing. The results of the study showed that the total income received by farmers from red pepper farming per planting season with an average land area of 540 m2 in the study area was Rp 22,400,000.00. The production cost of chili farming in Kebon Enha Lima, Pelalawan District, was IDR 13,247,740.00, resulting in a net income of IDR 9,152,260.00. Chili farming is quite profitable from an economic perspective. This can be seen from the R/C value of 1.69, which means that for every Rp 1.00 spent, a return or profit of 1.69 is obtained. The marketing channels for cayenne pepper at Kebon Enha Lima are direct and indirect marketing. The farmer's share value of all channels is said to be efficient, with the percentage of level I marketing channels at 50.00% and level II marketing channels at 100%.